Investigation on the fluctuation characteristics and its influence on impact force of supercritical carbon dioxide jet. (15th August 2022) - Zhang, Huidong; Liu, Yong; Tang, Jiren; Liu, Wenchuan; Chen, Changjiang
Abstract: Supercritical carbon dioxide (CO2 ) jet-assisted drilling is considered a promising technology in unconventional natural gas drilling engineering. The flow field characteristics of the supercritical CO2 jet are the critical factors that affect the erosion performance of the jet. The relation between the flow fluctuation characteristics and the jet is required further investigation to enhance its erosion performance. In this study, the fluctuation features of a supercritical CO2 jet were simulated based on a modified real gas model. Subsequently, impact force tests were conducted using an I-Scan flexible array pressure sensor to obtain peak pressures at different standoff distances. The results indicated that the flow field structure of the supercritical CO2 jet exhibits typical compressible wave-like features, which can be accurately determined by the expansion ratio. The expansion ratio was mainly affected by the inlet pressure, inlet temperature, and ambient pressure. The static pressure, temperature, and velocity distributions of a free jet could be significantly influenced by the fluctuation characteristics. Among them, the static pressure and temperature trend decrease in the expansion waves and increase in the compression waves, while the velocity shows a contrary variation trend. When the jet was under-expansion, the lengths of the wave node and jet potential core increased with increasing inlet pressure and decreased with increasing inlet temperature and ambient pressure. Moreover, the fluctuation characteristics of the flow field significantly affected the peak impact force of the supercritical CO2 jet. The peak impact force at the compression wave positions tended to be higher than that at the adjacent expansion wave positions. The maximum pressure difference of jet impact was 7.39 MPa in this study, which occurred when the standoff distance was 23.0 and 17.3 mm and accounts for 18.6% of the impact pressure at 23.0 mm. A plate shock wave was observed ahead of the target when the standoff distance was larger than 23.0 mm, which accounted for the abrupt decrease in pressure at the stagnation region. Highlights: The flow field of a supercritical CO2 jet has fluctuation characteristics. The impact force is significantly influenced by the fluctuation characteristics. The fluctuation characteristics are mainly determined by the expansion ratio.